The Effectiveness Test of Imunostimulants with Black Cumin Oil Extract (Nigella sativa) in Male Mice (Mus muscullus) - Nurhidayanti Nurhidayanti; Trimin Kartika (Universitas PGRI Palembang, 2021)
Background: The immune system is closely related to leukocytes. Leukocytes are part of the immune system which have an important role in every disease-causing agent. One of the efforts that can be made to increase the immune response is to provide an immunomodulator, a substance that can improve the immune system by means of stimulation (immunostimulants). Black cumin is able to stimulate bone marrow and immune cells and is able to protect normal cells from damage by disease agents, an increase in the total number of blood cells and their differentiation. Objectives: The purpose of this study was to determine the effect of giving black cumin oil extract on leukocyte levels in male mice. Methods: This type of research is experimental, to see the levels of leukocytes, after being treated with doses of 150 mg/kgBB, 300 mg/kgBB and 600 mg/kgBB for 21 days. The data obtained were then analyzed statistically using the ANOVA test. Result: The results obtained by the total number of leukocytes on day 7, day 14 and 21 showed a significant difference (p <0.05) for each treatment group. The use of black seed oil extract is very effective for boosting the immune system or immunostimulating. Conclusion: The benefit of this research is that it can provide information to the public that black cumin oil extract can be used as an alternative in increasing the body's immune system.Â Keywords: immunostimulants, black cumin, male mice